Three-component addition of terminal alkynes, carboxylic acids, and tert-butyl hypochlorite - Zhang, Xitao; Zhang, Sheng; Li, Shihong; Feng, Xiujuan; Yamamoto, Yoshinori; Bao, Ming (Chemical Communications, 2022)
This paper described the unprecedented three-component addition of terminal alkynes, carboxylic acids, and tert -butyl hypochlorite. This new type of addition proceeds smoothly to produce gem -dichloroalkane derivatives in satisfactory to excellent yields via successive two-time additions under mild conditions. The synthetically useful functional groups, such as Cl, Br, CN, and NO 2 , remained intact in the final products.